Cubozoan genome illuminates functional diversification of opsins and photoreceptor evolution - Liegertová, Michaela; Pergner, Jiří; Kozmiková, Iryna; Fabian, Peter; Pombinho, Antonio R; Strnad, Hynek; Pačes, Jan; Vlček, Čestmír; Bartůněk, Petr; Kozmik, Zbyněk (Scientific reports, 2015)
Animals sense light primarily by an opsin-based photopigment present in a photoreceptor cell. Cnidaria are arguably the most basal phylum containing a well-developed visual system. The evolutionary history of opsins in the animal kingdom has not yet been resolved. Here, we study the evolution of animal opsins by genome-wide analysis of the cubozoan jellyfish Tripedalia cystophora, a cnidarian possessing complex lens-containing eyes and minor photoreceptors. A large number of opsin genes with distinct tissue- and stage-specific expression were identified. Our phylogenetic analysis unequivocally classifies cubozoan opsins as a sister group to c-opsins and documents lineage-specific expansion of the opsin gene repertoire in the cubozoan genome. Functional analyses provided evidence for the use of the Gs-cAMP signaling pathway in a small set of cubozoan opsins, indicating the possibility that the majority of other cubozoan opsins signal via distinct pathways. Additionally, these tests uncovered subtle differences among individual opsins, suggesting possible fine-tuning for specific photoreceptor tasks. Based on phylogenetic, expression and biochemical analysis we propose that rapid lineage- and species-specific duplications of the intron-less opsin genes and their subsequent functional diversification promoted evolution of a large repertoire of both visual and extraocular photoreceptors in cubozoans.
Keywords: Animals; AMP cyklický; biologická evoluce; mapování chromozomů; multigenová rodina; Chromosome Mapping; proteiny vázající GTP; Genomics; GTP-Binding Proteins; Photoreceptor Cells; genom; Genome; signální transdukce; messenger RNA; Opsins; Signal Transduction; opsiny; RNA, Messenger; Phylogeny; Cyclic AMP; exprese genu; zvířata; Biological Evolution; fylogeneze; fotoreceptory; Cubozoa; Gene Expression; genomika; Multigene Family